If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 9 = -7(x + 9) Reorder the terms: 9 + y = -7(x + 9) Reorder the terms: 9 + y = -7(9 + x) 9 + y = (9 * -7 + x * -7) 9 + y = (-63 + -7x) Solving 9 + y = -63 + -7x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + y = -63 + -9 + -7x Combine like terms: 9 + -9 = 0 0 + y = -63 + -9 + -7x y = -63 + -9 + -7x Combine like terms: -63 + -9 = -72 y = -72 + -7x Simplifying y = -72 + -7x
| 5/6(9-6)y= | | U=6i-4j-23k | | 4x*4x+2x*2x=30 | | y=x^4-32x^2-144 | | y+5=-0.6(x+2) | | d/dx(x^11) | | (x*x)-11x=-28 | | 14x+12+15x+5=180 | | y-5=-1.667(x+3) | | (x-2)*(x-2)=9 | | 29x+3+31x-3=180 | | 28x+1+27x+4=180 | | 7x=5(2x-1) | | x+90+110+x=180 | | 1000=w^3 | | y-0=2.66(x+3) | | 8x+3+9x-6=180 | | 5x/3-3y/3-2=4y/7 | | y-6=-1(x-6) | | -2(y+2)=7y-1+3(2y+5) | | CBA+BAC=ABC | | 1/ln2x | | ln(x)+ln(3)=ln(x-1) | | 5n-4n+4= | | 8x-4+7x+3=180 | | 15x+6+81=180 | | y+2*y-5=2y+2 | | -4(4u-4)+5u=7(u+4) | | y+3=-0.6(x+7) | | 12x-4+11x+3=180 | | -2(6x-8)+9x=6+2(6x-1) | | (4t+5)(7t+5)=-3t |